Woman Economic Activist Melirik Pengabdian Perempuan Fatayat NU Kota Surabaya - Musfiqo, Siti; Sukamto; Laili, Ummiy Fauziyah (Aktualisasi Pengabdian Masyarakat, 2023)
In raising the organization of girls in Nahdlatul Ulama Association, women can have a very important role and function in determining the activities and programs that suit the needs of women themselves, whether as a companion husband or role model for their sons and daughters as well as community service, especially in leadership in the family or in general in this beloved country, which is evidence that women play such an important role in building the nation. The girls' activity program of the Nahdelatul Ulama Association in Surabaya for the period 2015-2020 helped to enhance the role of women in the service of society in general. The programme of activities outlined in the outline of the Programme of Action has been realized in terms of real value in social life The women girls of the Nahdlatul Ulama Association in Surabaya City have great commitment and dedication to performing real service, so that they can participate in filling various areas of life with its various problems. Share this service in the meaning of the acculturation framework for religion, social, cultural, as well as economics. A good and correct understanding pattern in religion can generate and achieve good and sustainable benefit. The acceptance of the award as a companion in accelerating the trauma of the victims of the terrorist bombing in Surabaya, presented by the Mayor of Surabaya on November 10, 2019, is proof that the girls of the Association for the Renaissance of Scholars in the city of Surabaya have performed his services to the country